Voting behaviour and political culture among students - Omar, Muhamad Fuzi; Othman, Muhammad Hanif (Research Institute for Prgression of Knowledge, 2014)
The objectives of the study are to identify and rank the factors that influence students’ voting behavior, to determine the type of political culture among students and to discover the relationship between demographic variables with factors that influencing students’ voting behavior. The data are collected using survey questionnaires. This study is conducted by focusing on students at International Islamic University Malaysia (IIUM) prior to the students’ representative council election 2014. The number of respondents is 206 students. The methodologies used are descriptive statistics, factor analysis and non-parametric techniques using Kruskal-Wallis test. The results from factor analysis show four new factors which influence students’ voting behavior. Those factors are being labeled as 1) Manifesto, 2) Group Affiliation, 3) Candidates and 4) Status-Qua. The Kruskal-Wallis test results show that there are significant mean differences between years of study with group affiliation, type of faculty with group affiliation and students involvement in society with candidates.